Syrian refugees Women's urinary tract infection knowledge, attitudes, and practices in Al-Mafraq Governorate: A Cross-Sectional study - Salwa M. Al Obeisat; Bayan Ahmad Oleimat; Karimeh Alnuaimi; Salam Bani Hani; Sanaa AbuJilban; Abdulqadir J. Nashwan (Elsevier, 2024)
Background: Urinary tract infections (UTIs) are common health problems, especially among women, which can have significant impacts on the quality of life and health care costs. Knowledge, attitudes, and practices regarding UTIs can influence prevention and treatment outcomes. Objectives: This study aimed to assess Syrian refugee women's level of knowledge, attitudes, and practices toward UTIs in Al-Mafraq Governorate. The relationships between the selected demographics and the level of knowledge, attitudes, and practices of these women toward UTIs were also examined. Design: A descriptive-correlational study design. Settings: Data was collected from two clinics in Al-Mafraq Governorate. The actual names of the centers are withheld, but they represent primary healthcare providers in the region. Participants: 400 Syrian refugee women were systematically sampled for this study. Selection was based on visiting the clinics during the study period, with inclusion and exclusion criteria focused on age, nationality, and willingness to participate. Methods: Structured interview questions were used to gather data related to the participants' demographics, knowledge, attitudes, and practices regarding UTIs. Results: The majority of participants had secondary education or less (87.3 %). The mean knowledge score about UTIs was 41.26 %. Detailed knowledge scores were reported for UTI causes, transmission modes, symptoms, complications, and preventive measures. Conclusions: Syrian refugee women in Al-Mafraq Governorate displayed a limited understanding of UTIs. Many women self-reported signs and symptoms related to UTIs, indicating a potential health concern. The results emphasize the importance of initiating UTI-focused educational campaigns for this population.